Juridical Assessment of Collateral in Microfinance: A Statutory Approach: Penilaian Yuridis terhadap Agunan dalam Pembiayaan Mikro: Sebuah Pendekatan Hukum - Purwaningsih, Sri Budi (Rechtsidee, 2023)
This research investigates the juridical appraisal procedure employed by Microcredit Banks in Indonesia for land and building collateral. Utilizing a statute approach, the study scrutinizes both the subject (ownership status) and object (land location, boundaries, land status, and proof of ownership) of the collateral. The assessment also considers taxation aspects, including the Non-Tax State Revenue (NJOP) value, transaction price, and market price. The findings reveal that a comprehensive analysis incorporating these diverse aspects is necessary for accurate valuation. The study underscores the vital role of collateral evaluation in loan disbursement, emphasizing that banks need to ensure that collateral meets all credit security conditions. Consequently, in the event of borrower default, banks can legally seize the collateral to recoup the outstanding debt. The findings have implications for enhancing microcredit banking regulations and for bolstering the legal protections of both banks and borrowers.Highlights: Juridical appraisal procedure adopted by Microcredit Banks crucially considers both the subject and object of land and building collateral. Taxation aspects, including the Non-Tax State Revenue (NJOP) value, transaction price, and market price, are integral to the comprehensive evaluation of collateral. Ensuring that collateral meets all credit security conditions is a paramount step in loan disbursement, providing legal protections for banks to recoup outstanding debt in the event of borrower default. Keywords: Microcredit Banks, Collateral Evaluation, Juridical Assessment, Credit Security, Indonesian Banking Regulations.